An analysis of the perceived responsibility, authority, and delegation of authority, of district supervisors, principals, and head teachers in the division of Ilocos Sur - Rosario, Guillerma Vicerra 1924- (s.n.], 1967)
This study analyzed and determined the degree of perceived responsibility, authority, and delegation of powers exhibited by district supervisors, principals, and head teachers in the Division of Ilocos Sur in order to provide ways and means to better realize the goals of administration and supervision which have tasks that demand the ability to work for, by, and with people.